Influence of Classroom Management Style on Senior Secondary Students’ Performance in Jos North Local Government Area - Shittu Lukman Olayinka; Muhammad Ridwan (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2025)
This study examined the influence of Classroom management style on senior secondary students’ performance in Jos North Local Government Area. The study was guided by four objectives. Inline with these objectives the study answered four corresponding research questions and tested two null hypotheses. Extensive literature was reviewed. The research design employed was a survey research design specifically cross-sectional survey research design. The population of this study comprised 1,231 Senior Secondary School (SS II) students in the 22 registered public secondary schools in Jos North Local Government Area of Plateau State, Nigeria. From this population, a sample of 200 SS II students was selected from ten public secondary schools out of the 22 registered public using simple random sampling technique. The instrument used for data collection was a structured questionnaire titled "Students Questionnaire on Teachers' Classroom Management Style and Students’ Academic Performance Questionnaire" (SQTCM). Content validity was established for the instrument and internal consistency reliability was also established and reliability index of 0.76 was established. Data was analysed using descriptive and inferential statistics. Mean and standard deviation was used in answering the research questions while t-test was used in testing the hypotheses. The study revealed that, effective classroom management positively influences students' academic performance by creating an organised and focused learning environment among other things. the study recommended among other things that, teachers should adopt a balanced classroom management style that combines clear rule-setting with student involvement to create a conducive learning environment and enhance student engagement.